Neutralizing antibody test supports booster strategy for young individuals after SARS-CoV-2 Omicron breakthrough - Yichuan Yao; Yunru Yang; Qiqin Wu; Mengyao Liu; Wei Bao; Qiutong Wang; Meijun Cheng; Yunuo Chen; Yiting Yu; Yuan Cai; Mei Zhang; Jingxue Yao; et al. (European Journal of Medical Research)
Abstract Background The SARS-CoV-2 Omicron variant, since its initial detection, has rapidly spread across the globe, becoming the dominant strain. It is important to study the immune response of SARS-CoV-2 Omicron variant due to its remarkable ability to escape the majority of existing SARS-CoV-2 neutralizing antibodies. The surge in SARS-CoV-2 Omicron infections among most Chinese residents by the end of 2022 provides a unique opportunity to understand immune system’s response to Omicron in populations with limited exposure to prior SARS-CoV-2 variants. Methods We tested the levels of IgG, IgA, and IgM specific to the prototype SARS-CoV-2 RBD (receptor-binding domain) in blood samples from 636 individuals by chemical luminescence assay, ELISA and pseudovirus-based neutralization assay. Results Inoculation with inactivated prototype SARS-CoV-2 vaccines or recombinant protein vaccines showed higher IgG levels after infection than the unvaccinated individuals. Moreover, the age resulted in different IgG levels after the Omicron infection as IgG level of the patients aged > 60 years was lower than that of patients aged < 60 years. This indicates that the IgG induced by SARS-CoV-2 Omicron breakthrough infection was different between old and young individuals. We found that a booster dose of the prototype SARS-CoV-2 vaccine led to a significant increase in the neutralizing immune response against the prototype SARS-CoV-2 and helped induce neutralizing antibodies against BA.5 and BF.7 variants after an Omicron breakthrough infection in young individuals, which is different from a previous report on older people. Conclusions These data suggest that the prototype SARS-CoV-2 booster vaccination helps induce high levels of neutralizing antibodies against Omicron BA.5 and BF.7 variants after Omicron breakthrough infection in young individuals. Trial registration: This study is a purely observational study.